Profile of cold-formed steel for compression member design a basic combination performance - Septiropa, Zamzami; Hanim Osman, Mohd.; Baharuddin Abd. Rahman, Ahmad; Azreen Mohd Ariffin, Mohd.; Huda, Miftachul; Maseleno, Andino (International Journal of Engineering and Technology, 2018)
Experiment previously showed several findings that the strength of cold-formed steel cross-section are not the same, where web strength and flange strength do not give the same response when receiving the axial load. This occurs not only because of a shift in the center point of the force due to deformation of the cross section, but also due to different strengths in cross-section, especially on the web section and flange section. To find out more details of this case, the experiment carried out the tensile test for mechanics property and compression test with an axial load to find which parts are weaknesses, then used as a reference in combining the profile. The compression test results showed significant increase in compression capability between single profile with double profile back to back (Dbb) or double profile flange to flange (Dff) with ratio 1: 2.24 and 1: 2.44 respectively. There is a non-linear increase in the value of Aeff and Ieff when becomes combine profiles (double, quadruple, hexatruple), so this can be the basis for increasing the combine profile capacity to be able to withstand larger loads. This experiment can show a basic performance of CFS, where are weak section parts of a profile can be used as a reference to put combine profile to increase compression capacity. With a numerical analysis approach compared to the experimental results, the combination of Cold-formed steel profile is established as a column for the low-rise building structure.Â Â